Exploring the interaction between competitiveness of a country and innovation using Bayesian networks - Cinicioglu, Esma Nur; Ulusoy, Gündüz; Önsel Ekici, Şule; Ülengin, Füsun; Ülengin, Burç (Informa UK Limited, 2017)
ABSTRACTInnovation cannot be related only to some factors inherent in the environment of a country, nor is it a single entity to be managed without any linkages to the rest of the actors comprising the competitiveness of a country. World Economic Forum (WEF)’s competitiveness model consisting of 12 pillars and 19 sub-pillars is an attempt along these lines. By analysing the interaction between the Innovation pillar and the remaining 11 pillars and their sub-pillars comprising the competitiveness indicators, this paper aims to provide strategic guidelines to policy-makers who search for strategies to improve their country’s innovativeness level. For this purpose, WEF’s Global Competitiveness Index data for the period (2009-2012) is employed. The innovation performance of 148 countries is analysed using an integrated cluster analysis and a Bayesian Network (BN) framework. The use of BNs enables us to discover the probabilistic dependency structure of competitiveness indicators and its innovation performance...
Keywords: H Social Sciences (General); Sensitivity Analysis; Cluster Analysis; Bayesian Networks; Innovation; Competitiveness